Neutron Spectrum Measured by Activation Diagnostics in Deuterium Gas-Puff Experiments on the 3 MA GIT-12 Z-Pinch; IEEE Transactions on Plasma Science; Vol. 45, iss. 12 - Cikhardt Ja. Jakub; Klir D. Daniel; Rezac K. Karel; Shishlov A. V. Aleksandr Viktorovich; Cherdizov R. K. Rustam Koshalievich; Cikhardtova B.; Dudkin G. N. Gennadiy Nikolaevich; Fursov F. I. Fedor Ivanovich; Kokshenev V. A. Vladimir Alekseevich; Kravarik Jo. Jozef; Kubes P. Pavel; Kurmaev N. E. Nikolay Evgenjevich; et al. (2017, 2017)
Title screen